Abundance of Microplastics in Water and Sediment in Coastal Waters of Tanah Merah Village, Meranti Islands Regency - Saputra, Rengki; Amin, Bintal; Nedi, Syahril (Journal of Coastal and Ocean Sciences, 2026)
This study aims to analyze the types and abundance of microplastics in water and sediment between research stations and to examine differences in microplastic abundance across sediment depths in the coastal waters of Tanah Merah Village, Meranti Islands Regency. Samples were taken from three different locations: residential areas, fishing ports, and mangrove areas. The number of water and sediment samples from the three research stations was 27. Water quality parameters, including temperature, salinity, pH, and current velocity, were measured to assess the condition of the aquatic environment. The results showed that four types of microplastics were found, namely fragments, fibers, films, and pellets. The abundance of microplastics in seawater had an average value of 0.86 particles/L, with fragments being the most dominant type. Meanwhile, the abundance of microplastics in sediment had an average value of 1084.33 particles/kg of sediment, with fibers dominating. Based on sediment depth, the highest microplastic abundance was observed at station three in the 0-10 cm layer, with an average of 1010 particles/kg of sediment. The abundance of microplastics in water and sediment shows a significant difference. This is because there is a significant relationship between the abundance of microplastics in water and sediment